Towards an understanding of the relationship between counterfactual thinking and career aspirations. - Teo, Haw Yin. (2011)
The present study examined the relationships between counterfactual thinking, career aspirations, and action-state orientation. It was hypothesized that individuals who scored higher on measures of entrepreneurial and managerial motivation would engage in counterfactual thinking less frequently, and that this relationship would be mediated by the individual’s action-state orientation. The results indicate that (a) entrepreneurial motivation is significantly negatively related to the action-state orientation dimension persistence versus volatility, (b) managerial motivation is significantly negatively related to frequency of counterfactual thought and significantly positively related to the action-state orientation dimensions disengagement versus preoccupation and initiative versus hesitation, and (c) these action-state orientation dimensions mediate the relationship between managerial motivation and frequency of counterfactual thought. The implications of the findings are discussed.